Shift in Japanese policy towards preferential trade agreements and its impact on foreign merchandise trade - Pasierbiak, Pawel (The journal of contemporary issues in business and government, 2016)
The article examines whether Japan’s involvement in preferential trade agreements (PTAs) has benefited the country’s foreign merchandise trade. At first reluctant, from the beginning of 21st century Japan has become active in signing PTAs. The research confirms positive effects of PTAs on Japan’s foreign trade. After PTAs had been entered into force, Japan’s exports to partner countries improved. Although Japan currently runs a trade deficit with PTA countries in aggregate, positive trends in the trade deficits with individual countries are observed. Arguably, Japan will achieve a total trade surplus with PTA countries in the foreseeable future if the positive trend continues.